The prevalence and antimicrobial resistance profiles of bacterial isolates from meat and meat products in Ethiopia: a systematic review and meta-analysis - Andarge Zelalem; Mekonnen Sisay; Jessie L. Vipham; Kebede Abegaz; Ameha Kebede; Yitagele Terefe (International Journal of Food Contamination, 2019)
Abstract Background Foodborne diseases associated with the consumption of meat and its products are of public health significance worldwide. The study is, therefore, aimed to estimate the prevalence and the antimicrobial resistance profile of some bacterial pathogens isolated from meats and its products in Ethiopia. Methods Literature search was conducted from major electronic databases and indexing services including PubMed/MEDLINE, Google Scholar, Science Direct and WorldCat. Both published and unpublished studies addressing the prevalence and antimicrobial resistance profiles of some bacterial pathogens in meat and its products in Ethiopia were included for the study. Data were extracted with structured format prepared in Microsoft Excel and exported to STATA 15.0 software for the analyses. Pooled estimation of outcome measures was performed with DerSimonian-Laird random-effects model at 95% confidence level. Degree of heterogeneity of studies was presented with I2 statistics. Publication bias was conducted with comprehensive meta-analysis version 3.0 software and presented with funnel plots supplemented by Begg’s and Egger’s tests. The study protocol is registered on PROSPERO with reference number ID: CRD42018106361. Results A total of 27 original studies with 7828 meat samples were included for systematic review and meta-analysis. The pooled prevalence of Salmonella spp., E. coli O157:H7, Staphylococcus spp. and L. monocytogenes was 9, 5, 21 and 4%, respectively. Based on animal species, the prevalence of Salmonella in goat, mutton, beef, pork, chicken, and fish meat was 18, 6, 10, 11, 14 and 2%, respectively. The prevalence of E. coli O157:H7 in beef, mutton, goat and other animal meats was 6, 6, 3 and 21%, respectively. The prevalence of Staphylococcus spp. in beef and other animal meats was 21 and 22%, respectively. Based on the sample source, Salmonella prevalence in abattoir, butcher and market was 6, 36, and 11%, respectively. The E. coli O157:H7 prevalence in abattoir, butcher and market was 5, 6 and 8%, respectively. The bacterial isolates showed different antimicrobial resistance profiles against selected drugs. About 25% of the Salmonella spp. was resistant to ampicillin. Besides, 9% of Salmonella spp. and 2% of E. coli O157:H7 were found to be resistant to ceftriaxone. The pooled estimates showed that 10% of E. coli O157:H7 isolates were resistant to ciprofloxacin. Moreover, Salmonella spp. (6%), L. monocytogenes (5%) and E. coli O157:H7 (2%) were resistant to gentamicin. Conclusion This study revealed that pooled prevalence of bacterial pathogens is relatively high as compared to other countries and hence, there is a need to design intervention to ensure meat safety in the sector.